1996
DOI: 10.1182/blood.v88.8.2959.bloodjournal8882959
|View full text |Cite
|
Sign up to set email alerts
|

Recipient humoral immunity against leukoreduced allogeneic platelets is suppressed by aminoguanidine, a selective inhibitor of inducible nitric oxide synthase

Abstract: Leukoreduced allogeneic platelet transfusions have been previously shown to initially stimulate an in vitro cellular cytotoxicity and subsequently Induce the formation of immunoglobulin G (IgG) antidonor alloantibodies. To further characterize these responses and determine if they are related, recipient BALB/c H-2d mice were treated with aminoguanidine (AMG), a selective inhibitor of inducible nitric oxide synthase (iNOS), and transfused weekly with 2 x 10(8) C57BL/6 H2b platelets. In control, non-AMG-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…CD4 + T-cell activation correlates with alloantibody responses to transfused PLTs. 23,25,27,28 In addition, depletion of CD4 + T cells abrogates alloantibody induction by LR-PLT transfusion. 29 Finally, CD4 + T cells are required for the induction of T cells involved in BMT rejection across mHA barriers.…”
Section: Ctla4-ig Treatment Prevents Lr-plt Transfusion-induced Bmt Rmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 + T-cell activation correlates with alloantibody responses to transfused PLTs. 23,25,27,28 In addition, depletion of CD4 + T cells abrogates alloantibody induction by LR-PLT transfusion. 29 Finally, CD4 + T cells are required for the induction of T cells involved in BMT rejection across mHA barriers.…”
Section: Ctla4-ig Treatment Prevents Lr-plt Transfusion-induced Bmt Rmentioning
confidence: 99%
“…LR-PLT products were harvested as previously described, 11 and transfusion dose and schedule were based on existing protocols in mice. [23][24][25] Briefly, donor PLT-rich plasma was isolated by centrifugation and was passed over a neonatal high-efficiency leukoreduction filter (Purecell PL, Pall Corp., Port Washington, NY). LR-PLT transfusions contained 1 ¥ 10 8 total PLTs and were transfused through the tail vein.…”
Section: Leukoreduced Plt-rich Plasma Preparationmentioning
confidence: 99%
“…Previous reports have suggested that the production of NO by iNOS within recipient APCs plays a significant role. 14,15 The role of iNOS/NO in the immune system comprises both regulatory and effector functions. 29 The former includes immunosuppressive effects (e.g., inhibition of lymphocyte proliferation) and the latter includes immunopathologic effects (e.g., tissue destruction) and immunoprotective activities (e.g., killing of microbial pathogens).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, although it cannot be ruled out that the additional lack of hydrogen peroxide production in the GP91 PHOX KO mice may also play a role in the above processes, PLT transfusions are associated with high interferon responses. 14,15 When interferon is present, iNOS is significantly activated and generates large quantities of NO, and because of the high affinity of NO with superoxide, the ONOOpathway may be preferentially activated. [36][37][38] When NO reacts spontaneously with superoxide to form ONOO -, the latter is very efficient at nitrating and nitrosylating tyrosine (tyr-NO2) and cysteine (cys-SNO) residues, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation